Biometric Cashless Payment System - Twinkle Phukan, Parth Tiwari, Ghansyam Rathod, Shreyans Patel (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The major issue in the e-payment system is delivering security to the users in the backing business. Conventional techniques usually suffer from the issues, regarding incapability to identify whether the person who wants to access is authorized or a fraud (who duplicitous the identity of authorized person). Biometric frameworks work on physiological and behavioral parameters, also Biometric installment is utilized for different sorts of frameworks. Rather than the strain of keeping cards and remembering their troublesome security code we can just go for biometrics. This framework is very useful and secure as well as manageable, eliminating the use of watchword or mystery codes to recall. The biometric cashless payment system is a multimodal system in which all the transaction is done by using biometric signatures of the authorized person as a security code or key to access their accounts. The biometrics will be stored in the database and will be provided to the system for identification. The system is based on image processing, it recognizes a person via its face, iris, and fingerprints and allows them to access their account. This multimodal system will be quick, easy and highly secure, also a prominent appropriation of biometric installment framework if developed will drive down the cost of biometric users and in this way making it more reasonable to entrepreneurs.